The importance of labeling on Long Chan drink / Nurul Nazira Mohd Zain - Mohd Zain, Nurul Nazira (2015)
Food labeling is a useful tools which inform people about their food choices. The label also can help clearly show patient the difference that portion size can make. on top of this, labeling provide other essentials information such as any allergen contain within a product which is need to know information for all of those who suffer from allergies.